Safety Recommendations for Administering Intravenous Prostacyclins in the Hospital. - Kingman, Martha S.; Chin, Kelly (Critical Care Nurse, 2013)
Prostacyclins are a high-risk category of continuous intravenous infusions increasingly used in hospitals to treat advanced pulmonary arterial hypertension, a rare condition characterized by vasoconstriction and vascular proliferation of the pulmonary arteries. Prostacyclins are given in doses of nanograms per kilogram per minute and have a narrow therapeutic dosing range for each patient. Sudden increases or decreases in dose can be life threatening. Previous studies revealed errors in the administration of these high-risk infusions, which in some instances led to serious adverse events, including death. The literature was reviewed for safety measures in administration of high-risk intravenous medications and input was obtained from leading experts in pulmonary arterial hypertension to create a set of safety recommendations for infusion of prostacyclins.